Energy and exergy analyses of thin layer drying of seedy grapes in a forced solar dryer - Cakmak, Gulsah; Yildiz, Cengiz (Sila Science, 2012)
In this paper, the energy and exergy analyses of the drying process of seedy grapes via forced solar dryer were presented. In the developed drying system, an expanded-surface solar air collector, a solar air collector with Phase-Change Material (PCM) and drying chamber with swirl element have been particularly included. An expanded-surface solar air collector has been used to achieve high heat transfer and turbulence effect while a solar air collector with PCM has been used to perform the drying process even after the sunset. On the other hand, the swirl elements have been located to give the swirl effect to air flow in drying chamber. Using the first law of thermodynamics, the energy analyses throughout the drying process were estimated. Then, exergy analyses were determined by applying the second law of thermodynamics. The main values of energy utilization ratio were found to be as 43%,40%, 38%, 34%,32%, 28% and 32% and the values of exergy efficiency were found to be as 23%,38%, 37%, 39%,54%, 77% and 56% for the seven different drying state ranged between 0.5 m/s (non swirl element), 0.5 m/s, 1 m/s(non swirl element), 1 m/s, 1.5 m/s(non swirl element), 1.5m/s and drying with PCM. It was concluded that the exergetic efficiency increased while energy utilization ratio decreased with increasing drying mass flow rate.
Keywords: Solar dryer; Swirl element energy utilization ratio; Exergy analyses